Viral Encephalitis and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The role of viral meningitis in the cause of epilepsy is reviewed by researchers from Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India; and University of Malaya, Kuala Lumpur, Malaysia.